Static and free vibration analyses of moderately thick hyperbolic paraboloidal cross ply laminated composite shell structure. (August 2021) - Nath Thakur, Sandipan; Ray, Chaitali
Abstract: The main objective of this paper is to investigate the response behaviour of moderately thick hyperbolic paraboloidal laminated shells using C 0 finite element formulations based on Higher order Shear Deformation Theory (HSDT). The mathematical model of HSDT includes the thickness co-ordinate to radius of curvature ratio ( z/R ) as well as zero shear conditions at free surfaces of the shell. The finite element equations have been developed using eight noded isoparametric shell element with seven degrees of freedom per node. The Jacobian matrix used in the finite element procedure is formulated by considering the curvilinear coordinates of the shell element. The accuracy of the present HSDT is validated by comparing the obtained results with those available published 2D and 3D elasticity solutions. An extensive parametric study on static and free vibration analyses of moderately thick hyperbolic paraboloidal laminated shells has been carried out to study the performance of shell for various geometric configurations.